Perilaku Antar Sesama Siswa dan Upaya Guru dalam Menyikapinya - Mima Defliyanti Saragih; Joy Novi Yanti Lumbantobing; San Mikael Sinambela; Johan Pardamean Simanjuntak; Manotar Leryaldo Sinaga; Abdinur Batubara (Pusat Riset dan Inovasi Nasional, 2024)
Behavior between fellow students is an increasingly disturbing phenomenon in the school environment. This can have a negative impact on the mental and emotional health of students who are victims. In facing this problem, teachers have an important role in responding to it. Teachers' efforts to address behavior include an educational approach, fostering positive values, creating an inclusive and supportive environment, and providing an understanding of the importance of respecting differences. The type of research used is qualitative, a research model that uses descriptive data in the form of written or spoken language from people and actors who can be observed. This qualitative research is carried out to explain and analyze individual or group phenomena, events, social dynamics, attitudes, beliefs and perceptions. The conclusion is that, with the active role of teachers, it is hoped that the school environment can become a safe and supportive place for all students, without discrimination based on physical appearance.